Republic of Slovenia : 2017 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for the Republic of Slovenia. (IMF Staff Country Reports; Country Report ;, 2017)
This 2017 Article IV Consultation highlights Slovenia's fourth year of steady economic recovery, following decisive measures to address a looming banking crisis in 2013. Output and employment have risen considerably. The external position has strengthened, reflecting robust exports and strong tourism. The financial system has substantially improved in the past few years. Rising domestic demand and continuing strong exports will support projected growth of about 3 percent in 2017. Over the medium term, economic growth will converge to the estimated potential GDP growth rate of 1.75 to 2.00 percent. Higher growth is possible if policies increase investment, reduce labor skills mismatches, and boost total factor productivity growth.